공해물질 배출지수 단위간의 상호 변환을 통한 호환 배출지수의 유용성 고찰 - 이창언(Chang-Eon Lee); 유호현(Hohyun Yu); 박태준(Taejoon Park); 김한진(Hanjin Kim); 이중성(Jungseong Lee); 우경택(Kyungtaek Woo) (한국연소학회지, 2019)
This study presents an organized interconverting method between various pollutant units used in emission and regulation indexes. This method firstly converts some emission index into original index (mi/mf), and then it is converted to any indexes to be found using the interconverting factor (ICF) between these two indexes. For that purpose, information on the fuel composition and combustion conditions are required along with emission index. If we use the converted index expressed as measurement index (mg/m3) under the same combustion condition, it is possible to grasp the quantitative relationship between various indexes. Also, using the total mass of pollutants makes it possible to judge the influence of the regulation index of various equipment on ambient particulate matter. KCI Citation Count: 4